ESSENTIALISM AND CONSTRUCTIVISM IN APPROACHES TO DEFINING RELIGION - D. Kh. Dobrynin (Концепт: философия, религия, культура, 2019)
The article touches upon different approaches to religion's conceptualization. The author makes an attempt to check the accuracy of the proposition according to which many ways of conceptualization of religion are reduced to two main approaches. One of them is the normative approach; which is associated with essentialism. Another approach is dimensionalism; which originates in constructivism. The author comes to the conclusion that this thesis is not correct. The article identifies other coordinates in the light of which it is possible to correctly typologize a wide range of existing approaches to religion's conceptualization. The author considers dimensionalist's models of religion to oppose to those ways of religion's conceptualization which involve explicit genetic definitions. The latter group of approaches can be divided into normative and non-normative.The author proves the thesis that essentialism is not a necessary part of approaches which based on generic definitions of religion. One of the arguments in favor of this statement is the existence of such religion's conceptualization strategies; which derived from the constructivist paradigm. Moreover; the essen tialistic traits have been found in dimensionalist's models of religion. This fact testifies to the incorrectness of reduction of dimensionalism to the sum of constructivist approaches to the definition of religion.The author comes to the conclusion that many approaches to the definition of religion can be considered in two independent dimensions: on the one hand; there is a pronounced controversy between supporters of using of an explicit generic definition of religion and supporters of dimensionalist's models of religion; on the other hand; there is a confrontation between essentialist and constructivist paradigms; which are implemented in a plenty of contemporary attempts to define a religion.